2016
DOI: 10.1021/acs.langmuir.6b00013
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(0) Nanoparticle Formation, Stabilization, and Mechanistic Studies: Pd(acac)2 as a Preferred Precursor, [Bu4N]2HPO4 Stabilizer, plus the Stoichiometry, Kinetics, and Minimal, Four-Step Mechanism of the Palladium Nanoparticle Formation and Subsequent Agglomeration Reactions

Abstract: Palladium(0) nanoparticles continue to be important in the field of catalysis. However, and despite the many prior reports of Pd(0)n nanoparticles, missing is a study that reports the kinetically controlled formation of Pd(0)n nanoparticles with the simple stabilizer [Bu4N]2HPO4 in an established, balanced formation reaction where the kinetics and mechanism of the nanoparticle-formation reaction are also provided. It is just such studies that are the focus of the present work. Specifically, the present studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 183 publications
2
7
0
1
Order By: Relevance
“…In the literature, it states that the C-NPs are often the true catalysts that are suitable for use in various systems. 16,21,22 In the fifth step, the agglomeration of C and B particles results in the formation of a C-particle, in agreement with the general model proposed by Finke. 23,24 The best fit theoretical profile shows good agreement between mechanism 1 and the data obtained experimentally, where C-NPs are the true isomerization reaction catalyst.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the literature, it states that the C-NPs are often the true catalysts that are suitable for use in various systems. 16,21,22 In the fifth step, the agglomeration of C and B particles results in the formation of a C-particle, in agreement with the general model proposed by Finke. 23,24 The best fit theoretical profile shows good agreement between mechanism 1 and the data obtained experimentally, where C-NPs are the true isomerization reaction catalyst.…”
Section: Introductionsupporting
confidence: 86%
“…The proposed mechanism of this reaction differs from the conventional type reported in the literature. 6,[12][13][14][15][16][17][18] We demonstrated that in the case of a composite complex structure, the order of the reduction of metallic centers inuences the NPs self-assembly mechanism, and in its turn, affects the kinetic prole of isomerization reaction (1). Schematically speaking, the proposed kinetic model is as follows see Scheme 2 (mechanism 1).…”
Section: Introductionmentioning
confidence: 99%
“…Some decades ago, the generation process of crystalline materials has been studied and many relevant theories have been achieved. On the basis of the classical nucleation theory (CNT), the generation process of metallic nanocrystals can be divided into three stages, namely, prenucleation, nucleation, and growth, where detailed discussion of different theories has been taking place in fields of chemistry, physics and mathematics. To handle modern metallic nanoparticle formation phenomena, the Finke and Watzky (FW) 2-step nucleation mechanism, which has successfully dealt with many situations of metallic nanoparticle growth, is discovered. In the FW theory, metallic nanoparticles mainly go through slow, continuous nucleation and autocatalytic surface growth, and the reaction kinetics of nucleation and growth can be facilely separated.…”
Section: Introductionmentioning
confidence: 99%
“…Однак таке зростання полідисперсності частинок після диспергування нанопорошків срібла у воді можна вважати незначним, а самі порошки -придатними для використання у подальших дослідженнях, зокрема для перевірки їх каталітичної активності [24], як наповнювачів в електропровідних полімерних композиціях тощо. Імовірно, що великі розмір і полідисперсність частинок срібла, отримані за одноразового додавання 2,4 мл 0,4 М розчину AgNO 3 до золю зародків, спричинені неконтрольованими процесами гомогенної нуклеації, автокаталітичного росту, агрегації наночастинок срібла і вторинного росту утворюваних агрегатів [27] через надзвичайно високі концентрації реагентів -0,02 моль/л AgNO 3 і 0,08 моль/л N 2 H 4 . Однак для підтвердження такого припущення необхідним є проведення додаткових досліджень.…”
Section: таблицяunclassified